1999
DOI: 10.1111/1467-8551.00107
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Management Performance

Abstract: This paper attempts to provide some insight into the individual attributes underlying managerial performance. Managerial performance, like all aspects of human behaviour, is a function of both the personal attributes of the actor and the situation in which he or she exists. Managers work in a wide variety of situations and it is clear that job demands, job role, colleagues, organization systems and other situational factors will exert an influence on the behaviour of any individual manager. It is also reasonab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 11 publications
0
24
0
3
Order By: Relevance
“…Salgado and Rumbo (1997) found that neuroticism, conscientiousness, and a composite of all Big-Five factors were valid predictors of the criteria of job-problem ability, job motivation and overall job performance in a sample of Spanish financial services managers. Recent work carried out in the United Kingdom by Ferguson et al (2000), Robertson, Baron, Gibbons, MacIver, and Nyfield (2000) and Robertson, Gibbons, Baron, MacIver, and Nyfield (1999), provided further support on the validity of personality scales, as expressed by the FFM, questioning however the universal validity of conscientiousness across occupations and job levels (Robertson et al, , 2000. The present study will also serve as an exploration of the criterion-related validity of the FFM in a nonEnglish culture and language.…”
Section: The Five-factor Model Of Personality At Workmentioning
confidence: 57%
See 1 more Smart Citation
“…Salgado and Rumbo (1997) found that neuroticism, conscientiousness, and a composite of all Big-Five factors were valid predictors of the criteria of job-problem ability, job motivation and overall job performance in a sample of Spanish financial services managers. Recent work carried out in the United Kingdom by Ferguson et al (2000), Robertson, Baron, Gibbons, MacIver, and Nyfield (2000) and Robertson, Gibbons, Baron, MacIver, and Nyfield (1999), provided further support on the validity of personality scales, as expressed by the FFM, questioning however the universal validity of conscientiousness across occupations and job levels (Robertson et al, , 2000. The present study will also serve as an exploration of the criterion-related validity of the FFM in a nonEnglish culture and language.…”
Section: The Five-factor Model Of Personality At Workmentioning
confidence: 57%
“…The present measure was successfully used in a number of studies (e.g., Robertson et al, 1999Robertson et al, , 2000 as an overall job performance score eliciting internal consistency reliability of .86. It consists of six items where the supervisor has to indicate whether she/he agrees or disagrees with the behaviour described in a 5-point scale.…”
Section: Methodsmentioning
confidence: 99%
“…To the degree that the targeted job requires both types of planning, combining them in measurement under the more general heading of "Planning and Organizing" will obscure understanding of how and to what degree creativity contributes to managerial success. Along those lines, Robertson, Gibbons, Baron, MacIver, and Nyfield (1999) found that Conscientiousness predicts distinct managerial competencies in opposite directions. Similar results obtained for Extraversion.…”
Section: The Need For a Detailed Taxonomy Of Managerial Competencementioning
confidence: 98%
“…For the measurements of in role and extra-role performance two instruments were used: Robertson"s performance scale (Robertson et al, 1999;Robertson et al, 2000),and Smith"s extra-role performance scale (1983). Robertson's performance scale offers a global score for the individual formal job performance.…”
Section: Methodsmentioning
confidence: 99%